Aldo-keto Reductase 1B10 (AKR1B10) Suppresses Sensitivity of Ferroptosis in TNBC by Activating the AKT/GSK3β/Nrf2/GPX4 Axis - Shanli Wu; Gun Yang; Xiaosha Wen; Yi Lin; Shenglong Wang; Jing Wang; Quan Liu; Dixian Luo (Frontiers in Bioscience-Landmark)
Background: Aldo-keto reductase 1B10 (AKR1B10) is expressed in various malignant tissues. Several studies have highlighted the essential function of AKR1B10 in lipid metabolism and in the detoxification of lipid peroxides. The aim of this research was to explore the role of AKR1B10 in the susceptibility of MDA-MB-231 cells to ferroptosis. These cells serve as a model for triple-negative breast cancer (TNBC). Methods: Lentiviral transfection was used to establish stable cell lines with high or low expression of AKR1B10. Our model of ferroptosis used the ferroptosis activator RSL3, and the specific ferroptosis inhibitor ferrostatin-1 (Fer-1) to rescue cell death. Stable cell lines were treated with the specific inhibitor OSU-T315 directed against phosphorylation of Ser473 in protein kinase B (AKT) and Ser9 in glycogen synthase kinase 3 beta (GSK3β), either alone or in combination with RSL3. A fatty acid stress model was established using palmitic acid (PA) or arachidonic acid (AA), either in the presence or absence of serum starvation and with or without co-treatment with RSL3. Cell viability was evaluated with the cell counting kit-8 (CCK8) assay and lipid peroxidation levels by flow cytometry after staining with C11 BODIPY 581/591. Exploration of the underlying mechanisms was conducted through RNA sequencing and bioinformatics analysis. Western blotting was performed to evaluate protein levels, and quantitative real-time polymerase chain reaction (qPCR) was used to evaluate transcript levels. Results: Western blot and qPCR analyses validated the successful establishment of stable MDA-MB-231 cell lines with and without AKR1B10 overexpression. Cell viability and lipid reactive oxygen species (ROS) assays showed that AKR1B10 suppressed ferroptosis in the RSL3-induced cell death model. Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Set Enrichment Analysis (GSEA) analyses indicated the phosphatidylinositol 3-kinase (PI3K)-AKT pathway was likely to play a role in the underlying mechanisms. AKR1B10 increased the expression of glutathione peroxidase 4 (GPX4), thus potentially implicating the AKT/GSK3β/nuclear factor erythroid 2-related factor 2 (NRF2)/GPX4 pathway in the mechanism. These changes in protein levels were also observed by Western blot analysis after 6 h of RSL3 treatment. Under the influence of RSL3, the transcript levels of NRF2-related genes including GPX4, ferritin heavy chain 1 (FTH1), heme oxygenase 1 (HO-1), and NAD(P)H quinone dehydrogenase 1 (NQO-1) were significantly elevated in the AKR1B10 overexpression cell line, whereas that of prostaglandin-endoperoxide synthase 2 (PTGS2) was significantly reduced. Similar changes were observed after treatment with OSU-T315. AKR1B10 was found to suppress the sensitivity to ferroptosis induced by treatment with OSU-T315, PA, or AA. These phenomena were rescued by the ferroptosis inhibitor Fer-1. Conclusions: AKR1B10 appears to be an important mechanism protecting MDA-MB-231 cells from ferroptosis, possibly through the AKT Ser473/GSK3β Ser9/NRF2/GPX4 pathway. AKR1B10 may be a key factor underlying the therapeutic effect of RSL3 under different exogenous fatty acid microenvironments.